Tinjauan Yuridis Perbandingan Perlindungan Hukum Terhadap Korban Dan Pelaku Kejahatan Didasarkan Atas Asas Equality Before The Law - Luthfi Rafisqy; Kalief Haaziq (Universitas Sains dan Teknologi Komputer, 2023)
The meaning of poetry according to Lafamane (2020: 1) Poetry is a form of literary work that results from the expressions and feelings of poets with language that is bound by rhythm, dimension, rhyme, composition of lyrics and stanzas, and is full of meaning. In line with that, poetry according to Sumardi (in Lafamane: 2020) is a literary work with condensed, shortened language, and given a rhythm with a coherent sound and a selection of figurative (imaginative) words. Agree with Herbert Spencer (in Lafamane: 2020) poetry is a form of expressing ideas that are emotional by considering beauty. From some of these meanings, it can be concluded that poetry is an expression or feeling of the author that is bound by the elements of poetry and is arranged in an interesting language and is also made in a high enough imaginative manner so that it makes the reader interested in the poetry he makes.